Identification of Reference Buildings in Mediterranean Countries: The HAPPEN Project Approach - Manuel Rosales; Chrysanthi Efthymiou; Nikolaos Barmparesos; Panagiotis Tasios; José Manuel Salmerón Lissén; Margarita Niki Assimakopoulos (Applied Sciences, 2022)
This study’s scope is to collect and analyze all the needed information related to the residential building stocks in Mediterranean countries, especially those that participated in the framework of the HAPPEN project (Greece, Croatia, Cyprus, Italy, Slovenia, Spain, and France). A specific procedure was followed in order to conduct a coordinated evaluation of the residential building stock. The most important variables for a statistical examination of the building stock are outlined, as well as an approach for establishing reference buildings. National data for the seven participating nations were collected and evaluated using the prescribed methodology. The research findings identify six distinct reference buildings in each nation. More specifically, the most representative buildings were distinguished through a cross-country comparison of the obtained data, after classifying the buildings into different classes to which the same approach for deep renovation/refurbishment can be applied.